imX Experience Partners Discuss Manufacturing Trends.
Recently, Manufacturing Engineering sat down with Don Lane, president/CEO of Makino Inc. (Mason, OH), and Larry Schwartz, president and COO, Okuma America Corp. (Charlotte, NC) to talk about conditions in the machine tool market and the upcoming imX event that will be held in Las Vegas September 12-14.
Keywords: Manufacturing Trends